Randomized controlled trials: who fails run-in?. Issue 1 (December 2016) - Rees, Judy; Mott, Leila; Barry, Elizabeth; Baron, John; Figueiredo, Jane; Robertson, Douglas; Bresalier, Robert; Peacock, Janet
Abstract Background Early identification of participants at risk of run-in failure (RIF) may present opportunities to improve trial efficiency and generalizability. Methods We conducted a partial factorial-design, randomized, controlled trial of calcium and vitamin D to prevent colorectal adenoma recurrence at 11 centers in the United States. At baseline, participants completed two self-administered questionnaires (SAQs) and a questionnaire administered by staff. Participants in the full factorial randomization (calcium, vitamin D, both, or neither) received a placebo during a 3-month single-blinded run-in; women electing to take calcium enrolled in a two-group randomization (calcium with vitamin D, or calcium alone) and received calcium during the run-in. Using logistic regression models, we examined baseline factors associated with RIF in three subgroups: men (N = 1606) and women (N = 301) in the full factorial randomization and women in the two-group randomization (N = 666). Results Overall, 314/2573 (12 %) participants failed run-in; 211 (67 %) took fewer than 80 % of their tablets (poor adherence), and 103 (33 %) withdrew or were uncooperative. In multivariable models, 8- to 13-fold variation was seen by study center in odds of RIF risk in the two largest groups. In men, RIF decreased with age (adjusted odds ratio [OR] per 5 years 0.85 [95 % confidence interval, CI; 0.76–0.96]) and was associated with being single (OR 1.65 [95 % CI; 1.10–2.47]), not graduating from high school (OR 2.77 [95 % CI; 1.58–4.85]), and missing SAQ data (OR 1.97 [1.40–2.76]). Among women, RIF was associated primarily with health-related factors; RIF risk was lower with higher physical health score (OR 0.73 [95 % CI; 0.62–0.86]) and baseline multivitamin use (OR 0.44 [95 % CI; 0.26–0.75]). Women in the 5-year colonoscopy surveillance interval were at greater risk of RIF than those with 3-year follow-up (OR 1.91 [95 % CI; 1.08–3.37]), and the number of prescription medicines taken was also positively correlated with RIF (p = 0.03). Perceived toxicities during run-in were associated with 12- to 29-fold significantly increased odds of RIF. Conclusions There were few common baseline predictors of run-in failure in the three randomization groups. However, heterogeneity in run-in failure associated with study center, and missing SAQ data reflect potential opportunities for intervention to improve trial efficiency and retention. Trial registration ClinicalTrials.gov:NCT00153816 . Registered September 2005.